Molecular rotation in p-H2 and o-D2 in phase I under pressure - Freiman, Yu.A.; Tretyak, S.M.; Goncharov, Alexander F.; Mao, Ho-kwang; Hemley, Russell J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The orientational order parameter, rotational ground-state energy, and lattice distortion parameter (the deviation of the c/ a ratio from the ideal hcp value 1.633) in hcp lattice of phase I of p-H2 and o-D2 are calculated using a semi-empirical approach. It is shown that the lattice distortion in these J-even species is small compared with that found in n-H2, and n-D2. The difference presumably is caused by the J-odd species.